Complex Network of NKT Cell Subsets Controls Immune Homeostasis in Liver and Gut - Marrero, Idania; Maricic, Igor; Feldstein, Ariel E.; Loomba, Rohit; Schnabl, Bernd; Rivera-Nieves, Jesus; Eckmann, Lars; Kumar, Vipin (Frontiers in Immunology, 2018)
The liver-gut immune axis is enriched in several innate immune cells, including innate-like unconventional and adaptive T cells that are thought to be involved in the maintenance of tolerance to gut-derived antigens and, at the same time, enable effective immunity against microbes. Two subsets of lipid-reactive CD1d-restricted natural killer T (NKT) cells, invariant NKT (iNKT or type I NKT) and type II NKT cells present in both mice and humans. NKT cells play an important role in regulation of inflammation in the liver and gut due to their innate-like properties of rapid secretion of a myriad of pro-inflammatory and anti-inflammatory cytokines and their ability to influence other innate cells as well as adaptive T and B cells. Notably, a bi-directional interactive network between NKT cells and gut commensal microbiota plays a crucial role in this process. Here, we briefly review recent studies related to the cross-regulation of both NKT cell subsets and how their interactions with other immune cells and parenchymal cells, including hepatocytes and enterocytes, control inflammatory diseases in the liver, such as alcoholic and non-alcoholic steatohepatitis, as well as inflammation in the gut. Overwhelming experimental data suggest that while iNKT cells are pathogenic, type II NKT cells are protective in the liver. Since CD1d-dependent pathways are highly conserved from mice to humans, a detailed cellular and molecular understanding of these immune regulatory pathways will have major implications for the development of novel therapeutics against inflammatory diseases of liver and gut.